IMPLEMENTATION OF QUALITY CONTROL IN NEWSPAPER PRINTING COMPANIES - Lala Hucadinota Ainul Amri; Yunus Fitriadi; Achmad Firdaus Putra Pradissa (Kreator, 2019)
Newspaper printing production processes cannot be separated from the problems that affect printed results and excessive waste. So in a printing company, quality control is needed in order to get good printing results and minimize the amount of waste. The print quality results in a company have several shortcomings such as unsuitable colors, and difficulty to get the register when printing. Apart from the aforementioned shortcomings, there are also factors that cause excessive waste, namely scumming, register disturbances, not sharp printouts, set-off, ghosting, and broken paper. How to solve problems that affect print quality and excess waste by cleaning the ink roll, adjusting the leg according to the proof, adjusting the pressure cylinder pressure, and adjusting the volume of wetting water. From the problems found, the print quality results in a printing company need to be increased so that the amount of waste generated is not too much or too much.Keywords— Print Quality, Waste, Quality Control